Ecological responses of phytoplankton and bacterial communities to eutrophication in the Han River Basin - Chen, Yuanyuan; Cai, Fangtao; Qi, Zhiyuan; He, Tianqi; Fang, Jiao; Zhai, Dongdong; Liu, Hongyan; Xia, Ming; Hu, Zhangfeng; Que, Yanfu; Xiong, Fei; Zhu, Bin (Frontiers in Microbiology, 2026)
IntroductionThe Han River Basin, a critical water source for the South-to-North Water Diversion Project, faces escalating eutrophication pressures due to intensive anthropogenic activities. This study aims to systematically evaluate the ecological responses of phytoplankton and bacterial communities to eutrophication gradients, and to elucidate their interactions for guiding ecosystem restoration.MethodsWater samples were collected from 15 sites across the Han River Basin in July 2023. Phytoplankton composition was identified microscopically (6 phyla, 33 genera), and bacterial communities were characterized via high-throughput sequencing of the 16S rRNA gene. Trophic states were assessed using a modified Carlson’s Trophic State Index (TSI). Relationships between environmental variables (TN, TP, Chl-a, COD, etc.) and community structures were analyzed via Monte Carlo tests, redundancy analysis (RDA), and co-occurrence network analysis.ResultsEutrophication Status: 75% of sites were eutrophic (TSI: 42.5–66.0), with significant spatial variations in TN (1.10–6.00 mg/L), TP (0.010–0.29 mg/L), and Chl-a (0.86–70.00 μg/L). Community Shifts: Phytoplankton dominance transitioned from Bacillariophyta in low-TSI areas to Cyanophyta in high-TSI regions. Bacterial communities were dominated by Proteobacteria (>60% abundance), with diversity declining as eutrophication intensified. Environmental Drivers: Monte Carlo tests indicated Chl-a and COD as key drivers for bacteria (p < 0.05), while TN primarily influenced phytoplankton (r = 0.39, p < 0.01). Network Interactions: Co-occurrence networks revealed increased negative correlations (0.32% to 0.61%) and reduced modularity (0.641 to 0.558) under eutrophic conditions, suggesting intensified competition.ConclusionEutrophication filters species adaptability, leading to deterministic succession in phytoplankton and homogenization of bacterial communities. The rise in negative correlations underscores escalating resource competition, potentially destabilizing ecosystem functions. Our findings emphasize the urgency of nutrient load reduction and adaptive management. Future studies should prioritize leveraging phytoplankton-bacterial synergism for bioremediation and resilience enhancement.